Improving the performance of production operations through Statistical Quality Control: Case study in South Mineral Water Company in Basra - Al-Malki, Afrah (South Asian Journal of Social Sciences and Humanities, 2024)
High-quality services and products give organizations a competitive advantage. Good quality reduces correction costs, waste, complaints and returns on defective products, and most importantly, it achieves customer satisfaction. Quality is the most important factor that affects the performance of an organization's production operations compared to its competitors. The main objective of this study is to use some statistical tools such as (X-bar Chart), which is one of the process control charts. In addition to using the ANOVA technique, this is among the statistical instruments employed to measure and analyses variance and identify sources of discrepancies between group averages. These tools were used in this study to monitor and control the quality of the production process to ensure that the products meet the required quality standards, and to identify and correct any problems or deviations from those standards as early as possible in the production process. The data collected from South Mineral Water Company was processed using the manual method as well as the Excel program. The research concluded that there was a variation in the level of water volumes inside the bottles within the sample as well as between the study samples, and after using the Tukey HSD equation, the largest difference between the variations was identified, which was between the average of observations 3 and 4, which had a value of 12.74.
Keywords: Mean X-bar Chart; Control Chart; Variance; ANOVA; One-Way variance analysis; Quality; Operation Performance